Endovascular stroke treatment in a small‐volume stroke center. Issue 4 (28th February 2017) - Behzadi, Gry N.; Fjetland, Lars; Advani, Rajiv; Kurz, Martin W.; Kurz, Kathinka D.
Abstract: Introduction: Our purpose was to evaluate the safety and efficacy of endovascular treatment (EVT) of stroke caused by large vessel occlusions (LVO) performed by general interventional radiologists in cooperation with stroke neurologists and neuroradiologists at a center with a limited annual number of procedures. We aimed to compare our results with those previously reported from larger stroke centers. Patients and Methods: A total of 108 patients with acute stroke due to LVO treated with EVT were included. Outcome was measured using the modified Rankin scale (mRS) at 90 days. Efficacy was classified according to the modified thrombolysis in cerebral infarction (mTICI) scoring system. Safety was evaluated according to the incidence of procedural complications and symptomatic intracranial hemorrhage (sICH). Results: Mean age of the patients was 67.5 years. The median National Institutes of Health Stroke Scale (NIHSS) on hospital admission was 17. Successful revascularization was achieved in 76%. 39.4% experienced a good clinical outcome (mRS<3). Intraprocedural complications were seen in 7.4%. 7.4% suffered a sICH. 21.3% died within 3 months after EVT. Discussion: The use of general interventional radiologists in EVT of LVO may be a possible approach for improving EVT coverage where availability of specialized neurointerventionalists is challenging. EVT for LVO stroke performed by general interventional radiologists in close cooperation with diagnostic neuroradiologists and stroke neurologists can be safe and efficacious despite the low number of annual procedures. Abstract : The use of general interventional radiologists in EVT of LVO may be a possible approach for improving EVT coverage where availability of specialized neurointerventionalists is challenging. Our results show that this approach can be safe and efficacious despite the low number of annual procedures.